The Role of Sustainability Orientation and Sustainable Environmental Performance in Improving Sustainable Economic Performance of the Batik Industry - Wibowo, Nugroho Mardi; Widiastuti, Yuyun; ‎ , Karsam; Pancawati, Iin (KnE Social Sciences, 2024)
The batik industry is starting to develop rapidly, and its contribution is improving the Indonesian economy. On the other hand, the batik industry produces waste that pollutes the environment. Batik SMEs do not realize the importance of sustainability orientation, and that some consumers prefer environmentally friendly batik products. The purpose of this study was to examine the relationship between sustainability orientation and sustainable economic performance, both directly and through sustainable environmental performance. The study was conducted in Surabaya, as well as the Regencies of Tuban, Lamongan, Sidoarjo, and Jombang. With the purposive sampling technique, 32 Batik SMEs were selected with 89 respondents. SEM-PLS was the method of data analysis used in this investigation. According to data analysis findings, sustainable economic performance benefits from sustainable environmental performance. Sustainable environmental performance is positively impacted by sustainability orientation. Sustainable economic performance is not directly impacted by sustainability orientation. Sustainability orientation indirectly influences sustainability economic performance through sustainable environmental performance. Increasing sustainability orientation can increase sustainable environmental and economic performance for realising the green batik industry. Keywords: sustainable development, sustainability orientation, sustainable economic performance, green batik industry